Comparative Genomics of Burkholderia singularis sp. nov., a Low G+C Content, Free-Living Bacterium That Defies Taxonomic Dissection of the Genus Burkholderia - Vandamme, Peter; Peeters, Charlotte; De Smet, Birgit; Price, Erin P.; Sarovich, Derek S.; Henry, Deborah A.; Hird, Trevor J.; Zlosnik, James E. A.; Mayo, Mark; Warner, Jeffrey; Baker, Anthony; Currie, Bart J.; et al. (Frontiers in Microbiology, 2017)
Four Burkholderia pseudomallei-like isolates of human clinical origin were examined by a polyphasic taxonomic approach that included comparative whole genome analyses. The results demonstrated that these isolates represent a rare and unusual, novel Burkholderia species for which we propose the name Burkholderia singularis. The type strain is LMG 28154T (=CCUG 65685T). Its genome sequence has an average mol% G+C content of 64.34%, which is considerably lower than that of other Burkholderia species. The reduced G+C content of strain LMG 28154T was characterized by a genome wide AT bias that was not due to reduced GC-biased gene conversion or reductive genome evolution, but might have been caused by an altered DNA base excision repair pathway. B. singularis can be differentiated from other Burkholderia species by multilocus sequence analysis, MALDI-TOF mass spectrometry and a distinctive biochemical profile that includes the absence of nitrate reduction, a mucoid appearance on Columbia sheep blood agar, and a slowly positive oxidase reaction. Comparisons with publicly available whole genome sequences demonstrated that strain TSV85, an Australian water isolate, also represents the same species and therefore, to date, B. singularis has been recovered from human or environmental samples on three continents.